The Work of the Brazilian Sign Language Interpreter at School: a case study - Keli Simões Xavier Silva; Ivone Martins de Oliveira (Universidade Federal do Rio Grande do Sul, 2016)
This paper analyzes the work of an educational Libras (Brazilian Sign Language) interpreter in a 7th grade classroom, in an inclusive school belonging to the Municipal School System from Vitória, Espírito Santo. Some results can be highlighted from the discussion carried out: first of all, it is emphasized that, although the Libras interpreter is not the teacher, it is necessary to be somehow involved with the educative work regarding interpretative acting; the work must be collaboratively planned with the sponsor teacher; the training for the interpreters who choose to work in the education field must deal with, besides being fluent sign language communicators, aspects concerning the school function, as well as the pedagogical mediation role in the knowledge appropriation process of the deaf student. Finally, the research indicates the need to enhance the discussion on the interpretation work specific features in the educational space.